THE EFFECT OF SELF-REGULATED LEARNING THROUGH ONLINE TUTORIALS INTEGRATING LEARNING STRATEGY IN IMPROVING THE INDEPENDENCE AND ACADEMIC ACHIEVEMENT OF BIOLOGY EDUCATION STUDENTS - Rahayu, Ucu; Widodo, Ari; Redjeki, Sri (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
The students of long distance education were demanded to had high self-regulated learning so that they could survive and success in their study. Therefore, they had to be trained to do self-regulated learning so that they could improve their academic achievements. This research was a quasi-experimental research involved 63 the students of long distance education of Biology Education who got used to do self-regulated learning through online tutorials integrating learning strategy and were given a guide of self-regulated learning and 48 the students who did not receive the treatments. After the online tutorials finished, the students filled the scale of self-regulated learning and had final exams. Besides, they filled open ended questioners and were interviewed. Based on the statistical results, the students who got self-regulated learning through online tutorials integrating the learning strategy and the learning guide significantly got higher score of self-regulated learning compared to the students who did not. Likewise the students' academic achievements were significantly higher than the students without treatments. In the future, it was suggested that the integration of the learning strategy into online tutorials should be done to all courses so that the students could had higher self-regulated learning influenced the academic achievements.